Revitalising Religiousness in the Mesanggok Hamlet through Religious Social Activities - Askar Rizki (Tabéq Care Center and UIN Mataram, 2025)
This study aims to analyse the increase in religiousness among the people of the Mesanggok hamlet through regular religious social activities. Previously, the level of religious observance in this village was relatively low, with many people neglecting their religious obligations and lacking knowledge of their faith due to their busy worldly lives. A qualitative approach was employed, utilizing data collection techniques that included observation, interviews, and documentation. The collected data were analysed descriptively with triangulation to ensure the validity of the information. The results of the study indicate that regular religious social activities, such as religious lectures, sholawat, dzikir, yasinan, and commemorations of important Islamic days, significantly increased the religiosity of the community. This improvement is reflected in increased participation in religious gatherings and sholawat, enhanced religious knowledge, and the application of religious values in social life, such as kindness, honesty, and mutual respect. The primary supporting factors are identity crisis and social change, while the main obstacles are the impact of globalization on the mindset of the younger generation.